Improved adsorption-desorption extraction applied to the partial characterization of the antilisterial bacteriocin produced by Carnobacterium maltaromaticum C2 - Tulini, F. L. (Sociedade Brasileira de Microbiologia, 2010)
Bacteriocins are ribosomally produced peptides useful for food biopreservation. An improved adsorption-desorption process is proposed for the partial purification of the bacteriocin produced by the fish isolate Carnobacterium maltaromaticum C2. Analyzis of extract by SDS-PAGE indicated this method may offer an alternative to improve the yield of purification of bacteriocins.